Absenteeism, Presentism and Academic Performance in Students from Peruvian Universities - Chafloque Céspedes, Raquel (2018)
The objective of this research was to determine the effect of absenteeism and presenteeism on the academic performance of undergraduate students from the Business and Engineering Schools in Peruvian Universities. The study is based on a self-report survey of 8,203 students from the business and engineering schools of Peruvian universities. Scales were used to analyze absenteeism, presenteeism and academic performance that showed suitable psychometric properties. The results showed that presenteeism has a higher impact on the academic performance of students (β = 0.628) compared toabsenteeism (β = 0.101). Absenteeism has a greater effect on courses and disapproved terms (Beta = 0.163) and presenteeism, on the evolution of academic performance (β = -0.145). Finally, by means of a model of structural equations, the causal structure of the academic performance decrease from absenteeism and presenteeism is proven.